Thermal design of air cooled condenser of a solar adsorption refrigerator - Amar Rouag; Adel Benchabane; Adnane Labed; Nora Boultif (Journal of Applied Engineering Science and Technology, 2016)
The objective of this paper is to study the design of a condenser of a solar adsorptionrefrigerator which will be tested in the region of Biskra (Algeria). The LMTD (log mean temperaturedifference) method is used to calculate the size of the condenser applying experimental dataobtained from the literature. For this purpose, a calculation code has been developed todetermine the total heat transfer area of the heat exchanger. Therefore, we present a comparisonbetween calculated and experimental results obtained from the literature. This comparisonallowed the validation of the calculation method by applying the same experimental conditions.The discussion of the results indicates that we cannot use the ambient air in free convection modeas a cooling fluid if its temperature exceeds 30°C. This problem presents the greatest obstacleespecially in the Saharan regions, such as in Biskra, where the average ambient air temperatureduring the summer exceeds 35°C. As a solution, we propose in this article the improvement of theheat transfer by the air-forced convection mode. Thus, it is established that the use of the air fancan extend the operating temperature limits of the condenser above 35°C.